Buying a product for an anticipated consumption situation. Issue 4 (11th November 2014) - Hirche, Martin; Bruwer, Johan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this study is to measure the product involvement of wine buyers and to examine relationships with anticipated consumption situations, places and occasions combined with the buyer's importance of various extrinsic product attributes. Design/methodology/approach – A survey is conducted with 147 wine buyers using structured self-administered questionnaires in a central city retail location in Australia. Findings – There are no significant relationships between consumers' involvement with wine products and what occasion or constellation of persons is anticipated when purchasing wine in a retail store. From a consumption situation perspective, both high- and low-involved buyers primarily anticipate consuming their wine together with other persons, mainly with food. High-involved wine consumers tend to consume their wine alone compared to low-involved consumers who are more likely to buy wine for other persons than for themselves. Regarding the product attributes that play an important role in retailing, this study finds that the importance of grape variety, the origin of the wine, the brand, the vintage, awards/medals and the product design increases with growing involvement in wine. The age of the buyer/consumer and the envisaged consumption occasion also affect the importance of various product attributes. We also find that wine buyers would spend on average over 15 more per unit when the wine is not bought for their personal consumption (e.g. gift). Originality/value – This study is of value to academic researchers, the wine industry in general and wine retailers in specific as it offers new insights on the role of product involvement and anticipated consumption situations when buying a product and their effects on the importance of product attributes.